Dobro moralne a autentyczna realizacja człowieka - Tomasz Grzywacz (Jesuit University Ignatianum in Krakow, 2017)
Theawarenessofbeingahuman,aswellasthecommitment to self-realization, constitute the basis for morality as such and  the element of creation of moral responsibility. Man's morality consists in realizing his free and conscious personal responsibility, which refers only to the interpersonal reality of human existence.Moralexperiencereferstothesubjectassuch,tohis experienceofconsciousness,freedomandresponsibility.Person self-defines himself/herself only thanks to the reason and free will.Itmeansthateverymoralrequirementhastobeaccessible and understandable for human reason. The author emphasizes that both personal and moral realization of oneself does not take place exclusively on the level of transcendental self-consciousness, but requires a reference to theobjectiveandrealworld.Thebasicplaceforethicalexperiencecanonlybeameetingwithotherness.Only in the face of the presence of personal "you" can man experience himself as an existentialunityofhowheunderstandshimselfandtheworld,his decisionsandwhohebecomesasaresultofthem.Onecanbe responsible only in front of personal "you". For we cannot talk about the experience of authentic values not referring to the experience of "the second person". In the case of lack of this experience, we deal with the total lack of moral experience.